Twenty years of newborn screening for congenital adrenal hyperplasia and congenital primary hypothyroidism: experiences from the DGKED/AQUAPE study group for quality improvement in Germany - Hammersen, Johanna; Bettendorf, Markus; Bonfig, Walter; Schönau, Eckhard; Warncke, Katharina; Eckert, Alexander J.; Fricke-Otto, Susanne; Palm, Katja; Holl, Reinhard W.; Wölfle, Joachim (Medizinische Genetik, 2022)
Congenital primary hypothyroidism (CH) and congenital adrenal hyperplasia (CAH) are targeted by the German and Austrian newborn screening. For both diseases, there are registries for quality improvement, based on standardized observational data from long-term patient follow-up, under the auspices of the DGKED study group. By September 2021, the CH registry HypoDOK includes datasets from 23,348 visits of 1,840 patients, and the CAH registry contains datasets from 36,237 visits of 1,976 patients. Here, we report on the recruitment process, patient characteristics, and research contributions from the registries, and underline that the registries are an important tool to improve patient care and outcomes. Registries for rare conditions should thus be considered as an important public health measure and they should be adequately institutionalized and funded.